National prevalence of IC/BPS in women and men utilizing veterans health administration data - Anger, Jennifer T.; Dallas, Kai B.; Bresee, Catherine; De Hoedt, Amanda M.; Barbour, Kamil E.; Hoggatt, Katherine J.; Goodman, Marc T.; Kim, Jayoung; Freedland, Stephen J. (Frontiers in Pain Research, 2022)
Importance Interstitial cystitis/bladder pain syndrome (IC/BPS) is an immense burden to both patients and the American healthcare system; it is notoriously difficult to diagnose. Prevalence estimates vary widely (150-fold range in women and >500-fold range in men). Objectives We aimed to create accurate national IC/BPS prevalence estimates by employing a novel methodology combining a national population-based dataset with individual chart abstraction. Study design In this epidemiological survey, all living patients, with ≥2 clinic visits from 2016 to 2018 in the Veterans Health Administration, with an ICD-9/10 code for IC/BPS (n = 9,503) or similar conditions that may represent undiagnosed IC/BPS (n = 124,331), were identified (other were controls n = 5,069,695). A detailed chart review of random gender-balanced samples confirmed the true presence of IC/PBS, which were then age- and gender-matched to the general US population. Results Of the 5,203,529 patients identified, IC/BPS was confirmed in 541 of 1,647 sampled charts with an IC/BPS ICD code, 10 of 382 charts with an ICD-like code, and 3 of 916 controls. After age- and gender-matching to the general US population, this translated to national prevalence estimates of 0.87% (95% CI: 0.32, 1.42), with female and male prevalence of 1.08% (95% CI: 0.03, 2.13) and 0.66% (95% CI: 0.44, 0.87), respectively. Conclusions We estimate the prevalence of IC/BPS to be 0.87%, which is lower than prior estimates based on survey data, but higher than prior estimates based on administrative data. These potentially represent the most accurate estimates to date, given the broader and more heterogeneous population studied and our novel methodology of combining in-depth chart abstraction with administrative data.